Lectotypification and neotypification of names related to Banisteriopsis caapi (Malpighiaceae): a contribution to understanding of Ayahuasca - de Souza, Raniely Miranda; Fagg, Christopher William; Sonsin-Oliveira, Júlia; Gonzaga, Augusto Francener Nogueira; de Oliveira, Regina Célia (Phytotaxa, 2023)
Banisteriopsis is a taxonomically complex genus, with 57 species in the New World. The best-known species of the genus is Banisteriopsis caapi, culturally important as the principal component of Ayahuasca tea, used in religious ceremonies by the native peoples in the Northwestern Amazon, and now expanded worldwide. A study of the species and names related to a strongly supported clade which includes B. caapi is being undertaken in this paper. Here, we provide four lectotypifications and a neotypification, as no original material species appear to be extant, as well as images of the selected lectotypes.